Fluxus, : the most radical and experimental art movement of the sixties - Ruhé, Harry (Amsterdam : A Amsterdam, 1979)
Albrecht, Dietrich ; Alocco, Marcel ; Andersen, Eric ; AY-O ; Ben ; Berner, Jeff ; Beuys, Joseph ; Bozzi, Robert ; Brecht, George ; Brouwn, Stanley ; Cage, John ; Caspari, Carlheinz ; Cavanaugh, John ; Chiari, Giuseppe ; Christiansen, Henning ; Corner, Philip ; Cox, Anthony ; Erébo, Robert ; Filliou, Robert ; Fine, Albert M. ; Flynt, Henry ; Friedman, Ken ; Gosewitz, Ludwig ; Grimes, Bob ; Gysin, Brion ; Hansen, Al ; Hashimoto, Sohei ; Heflin, Lee ; Hendricks, Bici ; Hendricks, Geoffrey ; Hi Red Center ; Higgins, Dick ; Hompson, Davi Det ; Hutchins, Alice ; Ichiyanagi Toshi ; Johnson, Ray ; Jones, Joe ; Kennedy, Peter ; Kirkeby, Per ; Klintberg, Bengt af ; Knizak, Milan ; Knowles, Alison ; Köpcke, Arthur ; Kosugi, Takehisa ; Kubota, Shigeko ; Landow, George ; Landsbergis-Zemkalnis, Vytautas ; Lauffer, Dan ; Lennon, John ; Lens, Bob ; Lieberman, Fred ; Ligeti, György ; Liss, Carla ; Mac Low, Jackson ; Maciunas, George ; de Maria, Walter ; Mathews, Joan ; Maxfield, Richard ; Mekas, Jonas ; Mengelberg, Misha ; Mercure, Pierre ; Miller, Larry ; Moineau, Jean-Claude ; Moore, barbara ; Moore, Peter ; Mosset, Olivier ; Oldenburg, Serge III ; Ono, Yoko ; Page, Robin ; Paik, Nam June ; Palazzoli, Daniela ; Patterson, Ben ; Pietkiewicz, Hala ; Raman, Ely ; Reynolds, Jock ; de Ridder, Willem ; Riddle, James ; Riley, Terry ; Roth, Dieter ; Saito, Takako ; Schippers, Wim T. ; Schmit, Tomas ; Schneemann, Carolee ; Sharits, Greg ; Sharits, Paul ; Shiomi, Mieko (Chieko) ; Simonetti, Gianni Emilio ; Spoerri, Daniel ; Szentjoby, Tamás ; Thompson, David ; Tone Yasunao ; Topor, Roland ; VanDerBeek, Stan ; Vostell, Wolf ; Wada, Yoshimasa ; Watts, Robert ; Wilhelm, Jean-Pierre ; Williams, Emmett ; Young, La Monte ; Zaj
Edities p. 3.II, bibliog. p. 3.III
Engels
boek